Low Cardiac Output Syndrome pada Anak Pasca Operasi Jantung Terbuka - PW Busro; EM Marwali; N Budiwardhana; CG Koto; PS Roebiono; AU Rahajoe; GM Harimurti; D Fakhri; J Rahmat (Jurnal Kardiologi Indonesia, 2007)
Background. A Low cardiac output syndrome (LCOS) was defined as poor perfusion due to transient myocardial dysfunction.The purpose of this study was to identify patients at risk for the development of LCOS in pediatric after cardiac surgery.Methods and results.The patient characteristics that were independent predictors of LCOS were identified among472 consecutive pediatric pa-tients who underwent cardiac surgery at the National Cardiovascular Center – Indonesia between January 2005 and December2005. The overall preva-lence of LCOS was 15.43 % (n= 73). Logistic regression analyses identified eight independent predictors of LCOS and calculated the factor-ad-justed odds ratiosassociated with each predictor: (1) residual lesion (odds ratio 141.98); (2) complexity score(odds ratio 1.74);(3) Cardiopulmonary bypass (CPB) time (odds ratio1.01); (4) preoperative Intensive Care Unit (ICU) (odds ratio 8.51); (5) preoperative Congestive Heart Failure (CHF) (odds ratio 3.14); (6) bleeding (oddsratio 24.88); (7) arrhythmia (odds ratio 4.78); and (8) pulmonary hypertension (odds ratio3.75). The opera-tive mortality rate was higherin patients in whom LCOS developed than in those in whom it did not develop (39.72% versus 0.75%, p<0.001). Mean basic complexity score was 6.25 with mortality rate 6.76, and the overall performance was 5.83.Conclusions. Compared to STS and EACTS, the performance of National Cardiovascular Center– Indonesia was still lower. LCOS caused longer time of intubation time, ICU and hospital stay. There were eight independents predictor that can be used to predicts LCOS in pediatric patients after open heart surgery. Patients at high risk for the develop-ment of low cardiacoutput syndrome should be the focus of more inten-sive management to prevent the development of LCOS.